NEWBORNS FUNGAL INFECTIONS: ASSOCIATED FACTORS AND CLINICAL-EPIDEMIOLOGICAL PROFILE - Frizzo, Ana Paula Machado; Caligiorne, Rachel Basques; Marques, Luciana Araújo; de Figueiredo, Sônia Maria; Marques-Silva, Thais Almeida (ARACÊ, 2025)
Objective: Invasive Fungal Infections (IFI) are among the main causes of morbidity and mortality in newborns. In this way, the objective of this research is to analyze the frequency of fungal infections in newborns admitted to the Neonatal Intensive Care Unit (NICU) in a public Hospital of Itaperuna city, Rio de Janeiro State, Brazil, identifying associated factors and describing its clinical and epidemiological characteristics. Study design: This is an observational, descriptive, and analytical study, with data collected from the medical records of hospitalized newborns. Subsequently, in order to identify the role of the variables as associated factors for neonatal fungal infection, a Multivariate Logistic Regression model was carried out using the presence of Candida spp. infection as the response variable. Comparative analyzes were carried out considering the odds ratio (OR), 95% confidence interval (95% CI) and p value, obtained during the bivariate logistic regression analysis. Results: This study consisted of 78 newborns patients, of which 23.08% (18/78) were positive for Candida species´ infection. In the final model, two factors were found to be associated with Candida spp. newborns fungal infections: caesarean delivery (OR:7.6; 95%CI:1.13-51.24) and exclusive parental nutrition for days (OR:1.1; 95%CI:1.03-1.17). Conclusions: Knowledge about newborns fungal infections associated factors can help to optimize these patients’ management, as well as contributing to reduce the high rates of fungal infections in this group of patients.